Pengaruh Sistem Pengendalian Internal Pemerintah dan Kompetensi Pegawai Terhadap Kinerja Instansi Pemerintah Kabupaten Karimun - Doni Putra Utama (Journal of Applied Accounting and Taxation, 2020)
This research is a causality study with the title "Effect of Government Internal Control Systems and Employee Competence on the Performance of Government Agencies in Karimun Regency." The purpose of this study was to determine the effect of the implementation of the Government's Internal Control System on the performance of Karimun Regency government agencies and to determine the effect of employee competence on the performance of Karimun Regency government agencies. Data collection using a questionnaire where the questionnaire contained questions about the Government's Internal Control System, employee competencies and agency performance. Data were tested using multiple linear regression statistical tests. Based on the results of the study, it can be concluded that the governmental internal control system has a significant positive effect on Government Agency Performance with the results of statistical tests that show a sig value of 0.016 <0.05 (alpha 5%). Employee Competency has a significant positive effect on Government Performance with the results of statistical tests showing a sig value of 0,000.